2011
DOI: 10.26719/2011.17.12.911
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B and C among barbers and their clients in the Rabat region of Morocco

Abstract: A cross-sectional seroepidemiological study was conducted in the Rabat-Salé-Zemmour-Zaër region of Morocco in 2007 among 267 barbers and 529 clients, all men with no history of hepatitis B (HBV) vaccination. The overall prevalence of HBV seropositivity was 28.1% in barbers and 25.1% in clients; 1.9% and 1.7% respectively had active HBV (HBsAg positive). Risk factors for HBV included older age, low educational level, urban living, being married, history of transfusion, lack of current heterosexual relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 15 publications
4
20
0
Order By: Relevance
“…Thus, we found that being a barber alone is not a potential risk factor for HBV infection, although the opposite has been shown in other countries (18, 20). Based on similar studies in other countries, the prevalence of HBsAg in Egyptian barbers and their clients is 4.2% and 3.9%, respectively, while the rates are 8.5% and 1.9% among Turkish and Moroccan barbers, respectively (18, 21, 22). …”
Section: Discussionmentioning
confidence: 82%
“…Thus, we found that being a barber alone is not a potential risk factor for HBV infection, although the opposite has been shown in other countries (18, 20). Based on similar studies in other countries, the prevalence of HBsAg in Egyptian barbers and their clients is 4.2% and 3.9%, respectively, while the rates are 8.5% and 1.9% among Turkish and Moroccan barbers, respectively (18, 21, 22). …”
Section: Discussionmentioning
confidence: 82%
“…A survey of anti-HCV antibodies among barbers and their clients indicated that the prevalence rate hovered above 5%, probably because of unsanitary conditions [34]. This problem could also exist in Libya, where most of the hairdressers are Moroccans.…”
Section: Epidemiology Of Hcv In the Maghreb Regionmentioning
confidence: 99%
“…Habits and cultural factors that may influence the spread of HCV in North African countries include male and female circumcision, particularly in Egypt, Sudan, Mauritania, and Morocco. Hijiama (bloodletting) done by informal practitioners, tattooing, folk body piercing and threading, sharing hygiene tools and sharp items, and the use of communal barbers may be considered as risk factors for HCV, particularly among rural dwellers [21, 34]. Education and public awareness campaigns are needed to teach the populations about the risks involved.…”
Section: Vectors Of Hcv Transmission In the North Africamentioning
confidence: 99%
“…Most studies have reported no significant difference in the HBV prevalence between barbers and the control group (determined by the presence of serum HBsAg) [17][18][19]. A study from Turkey reported a higher HBV prevalence among barbers; however, it is also important to consider its limitations [20].…”
Section: O R I G I N a L P A P E R In Abbasi Et Almentioning
confidence: 99%